Does acupuncture treatment modulate inflammatory cytokines in rodent models of depression? A systematic review and meta-analysis - Guo, Ziyi; Ren, Zhuoyu; Yao, Jianping; Li, Yamin; Che, Zhiying; Yu, Zhiyang; Fang, Peigang; Lu, Xiao; Chen, Min (Frontiers in Behavioral Neuroscience, 2024)
Background: Despite the increasing global prevalence of depression, existing treatment methods have limitations. Acupuncture has been recognized for its potential to alleviate various diseases by regulating inflammatory cytokines. However, a comprehensive systematic analysis of the effects of acupuncture on depression through inflammatory cytokines is currently lacking. This review aims to evaluate the impact of acupuncture on inflammatory cytokines in animal models of depression. Methods: A comprehensive search was conducted in PubMed, EMBASE, MEDLINE, and the Research Information Service System to identify studies that met predefined inclusion and exclusion criteria. The quality of each included study was assessed using a 10-item checklist adapted from the Cochrane Collaboration methods and animal data review. Meta-analysis was performed using STATA 17.0 software for literature that met the inclusion criteria.The meta-analysis included a total of 21 studies involving 376 rodents. The overall quality of the included reports was rated as moderate or higher. The results demonstrated that acupuncture had a significant effect on the reduction of pro-inflammatory cytokines, including: IL-1β [SMD = 3.36, 95% CI (2.73, 4.00), I 2 = 73.3%, P < 0.05], IL-6 [SMD = 3.05, 95% CI (2.45, 3.64), I 2 = 68%, P < 0.05], and 95% CI (2.53, 4.06), I 2 = 74.5%, P < 0.05]. Conversely, acupuncture was associated with an increased expression of anti-inflammatory cytokines, notably: IL-4 [SMD = -1.64, 95% CI (-2.46, -0.82), I² = 4.1%, P = 0.307] and IL-10 [SMD = -1.45, 95% CI (-2.24, -0.66), I² = 0, P = 0.678]. These results suggest that acupuncture modulates cytokine levels in depressed rodents, including reducing the expression of pro-inflammatory cytokines and increasing the expression of anti-inflammatory cytokines, thereby regulating the immune-related antidepressant pathway.While this study is limited by the number of included studies, the results suggest that acupuncture may be a viable option for the treatment of depression, and this effect is achieved through the regulation of various inflammatory cytokines.